Dissolution behavior and porous kinetics of limonitic laterite during nitric acid atmospheric leaching. (July 2022) - He, Fei; Ma, Baozhong; Wang, Chengyan; Zuo, Yian; Chen, Yongqiang
Highlights: DFT was introduced to describe the process of goethite dissolution. The Ni extraction could be described by a grain model-cylindrical particle. The activation energy and effective diffusivity of nickel extraction were obtained. Abstract: In our previous study, the mineral evolution and porous kinetics during nitric acid pressure leaching of limonitic laterite has been investigated. In order to optimize the nitric acid leaching technology, this paper investigated the dissolution behavior and porous kinetics of limonitic laterite during nitric acid atmospheric leaching. The experimental results showed that Ni and Fe had consistent leaching behavior, whereas Co was only consistent with Mn in the early stages of leaching. The DFT (Density functional theory) simulations of goethite dissolution revealed that H + attacked the bridging O first with adsorption energy of −1.37 eV, while NO3 – attacked the Fe with adsorption energy of −3.07 eV, hence promoting the dissolution of Fe from the goethite crystals. Based on meticulous modeling analysis, the leaching of Ni could be described by grain model-cylindrical particle. In the early stage of leaching, the Ni extraction is regulated by chemical reactions with an activation energy of 88.4 kJ/mol. In the latter stage, the leaching is regulated by pore diffusion with an effective diffusivity of 1.37 × 10 -11 m 2 /min at 90 °C. This study clarified the dissolution behavior of limonitic laterite, and described nickel leaching using a porous kinetic model.